PROSPECTIVITY OF RESEARCHES OF HIGHER EDUCATION IN THE PERIOD OF POSTPANDEMIA: THE RELEVANCE OF THE PROBLEM AND THE POTENTIAL OF RESULTS: COVID-19 pandemic; educational process; expected results; online teaching and learning; postpandemic period; project; research - Melnyk, Nataliia; Kovtun, Olena (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The COVID-19 pandemic has created a new paradigm of ‘life in social distancing’, which in its turn has had a massive impact on education. Most universities shifted from conventional, in-person, face-to-face instruction to online teaching and learning, which meant that syllabi, teaching approaches, tools of assessments and ways of teacher-student communication had to be modified to meet challenges of the altered mode of instruction. However, the pandemic situation will not last forever and global and national systems of higher education should be ready to meet the requirements of the post-pandemic period. Therefore, we see the objective of the paper in substantiating the relevancy and necessity for conducting research dedicated to forecasting challenges of post-pandemic higher education and ways to resolve them. The following set of methods was applied to achieve the research objective: an abstract-logical method that allowed to synthesize theoretical material and covered a variety of techniques (analysis, synthesis, ascent from the concrete to the abstract, comparison, hypothetical prediction and analogy); systematization and generalization of the obtained data (prognostic modeling) that made it possible to substantiate the relevance and necessity for forecasting transformational changes in the system of higher education, led to the development of the structure of the study, defined its scientific novelty and practical significance; and empirical methods (interviews with, experts, researchers and teaching staff, observation of the educational process), which allowed to predict further challenges and changes in the higher education system in the post-pandemic period. Main results lie in presenting a detailed project of the research “Higher education in the post-pandemic period: transformations, challenges and prospects”, its tasks, stages, theoretical novelty and practical significance, expected results. Conclusions. The relevancy and necessity for conduction in-depth research of post-pandemic challenges and potential of higher education system was substantiated